Analysis Of Factors That Influence Repurchase Intention Towards Purchasing Household Appliances Products In E-Commerce In The City of Batam - Sherlyca Styvani; Rizni Aulia Qadri; Renny Christiarini (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
E-commerce has radically changed commerce by facilitating shopping and selling without geographical or time constraints. This research aims to determine what makes online furniture shoppers more likely to buy from a specific retailer again. Information is obtained through surveys of Batam City residents who have made online home décor purchases. Researchers evaluated two kinds of data to give a comprehensive picture of the behaviors of internet shoppers: secondary data derived from literature reviews and primary data gathered through questionnaires. Four elements significantly impact customer satisfaction and repurchase intentions: perceived product value, perceived e-service quality, perceived product utility, and perceived product simplicity of use. Nevertheless, whether or not satisfied clients will return to you depends on factors other than their happiness. These findings increase our understanding of the mechanics of consumer behavior in this context and provide the foundation for improved strategies to affect consumer purchasing behavior through e-commerce platforms.